Fakoemulzifikace u katarakty po PPV (srovnání peroperacního prubehu fakoemulzifikace s pars plana infuzí a bez pars plana infuze) - Valesová, L; Hyel, J; Diblík, P (Ceska a slovenska oftalmologie, 2004)
PURPOSE: To compare peroperative complications of standard phaco technique and phaco with pars plana infusion performed for cataract after pars plana vitrectomy. METHOD: This prospective study randomly divided group of 64 patients with cataract after PPV into group A (standard phaco, 38 patients) and group B (phaco with par olana infusion, 26 patients). The study verifies the rate of peroperative complications such as deep anterior chamber, diaphragma movement miosis, and zonular dehiscention in these two groups. RESULTS: Peroperative complications had slightly higher rate in group B (with infusion). No specific complication in group A (standard phaco) was found. CONCLUSION: Standard phaco technic without par plana infusion has at least the same level of safety as phaco with pars plana infusion.
Keywords: Vitrectomy; Lens Implantation, Intraocular; peroperační komplikace; lidé; prospektivní studie; implantace nitrooční čočky; vitrektomie; Prospective Studies; Intraoperative Complications; Phacoemulsification; fakoemulzifikace; Humans